Prime Minister as Moral Crusader: Stephen Harper’s Punitive Turn in Social Policy-making - Prince, Michael J. (Canadian Review of Social Policy / Revue canadienne de politique sociale, 2015)
Stephen Harper has been Canada’s Prime Minister since 2006, heading three Conservative administrations; two minority governments (2006-08, and 2008-11) and one majority government (2011- to the present). Harper’s time in power has spanned periods of economic growth and surplus federal budgets, through a deep economic recession and budget deficits, to a tentative recovery of the Canadian economy and federal program of general fiscal restraint. Throughout this period of shifting economic and political circumstances, Harper, an intensely partisan and disciplined politician, has dominated his cabinet and parliamentary party as well as defined federal social policy and intergovernmental relations in particular ways. Like other Prime Ministers and governments, the Harper era exhibits a mixed pattern of social policy-making. Thus, although there are certain similarities in policies with previous federal administrations led by Liberal Prime Ministers, Harper’s social policy is distinctive as well. This article advances the argument that Harper’s characteristic approach can be understood in terms of an institutional-punitive conception of social policy. This stern approach to federal social policy-making involves the identification of dangerous persons and threatening behaviours, the elaboration of laws and creation of new offences, and the intensification of legal penalties and punishments. What emerges is the role of Prime Minister as moral crusader in a politics of fear, judgement and regulation. Stephen Harper est le premier ministre du Canada depuis 2006, et il a dirigé trois administrations conservatrices: deux gouvernements minoritaires de 2006-2008, et de 2008-2011, et un gouvernement majoritaire de 2011 à aujourd’hui. Ces administrations ont connues des périodes de croissance économique et de budgets fédéraux excédentaires, ainsi qu’une profonde récession économique, pour arriver enfin à une relance incertaine de l’économie canadienne et à un programme général fédéral de contraintes budgétaires. Harper est un politicien éminemment partisan et très discipliné, et il a dominé son cabinet ainsi que son parti parlementaire au cours de cette période de conditions économiques et politiques changeantes. Il a également redéfini la politique sociale fédérale et les relations intergouvernementales de manière spécifique. Comme d’autres premiers ministres et gouvernements auparavant, l’ère de Harper fait montre d’un mélange de motifs de politiques et de gestion sociales. Donc, bien qu’il existe de similarités en politiques sociales avec les administrations fédérales libérales qui l’ont précédée, la politique social de Harper est très distincte et cet article propose donc que l’approche caractéristique à Harper peut être définie comme une politique sociale institutionnelle-punitive. Cette approche sévère a propos des politiques sociales fédérales, incorpore un processus d’identification de personnes dangereuses et de omportements menaçants, la création de nouvelle lois et de nouveaux délits pour les contrôler, et, l’augmentation des sanctions et peines légales. Le rôle du premier ministre émerge donc comme celui d’un champion de la moralité, aidée par une politique de peur, de jugement et de règlementation. Mots-clefs: politique sociale fédérales; conservatisme moral; sciences politiques.